Human Resource Management Strategy in Organisational Digital Transformation - Silvy Sondari Gadzali; Junaid Gazalin; Sutrisno Sutrisno; Yanto Budi Prasetya; Abu Muna Almaududi Ausat (Jurnal Minfo Polgan, 2023)
In the rapidly evolving digital age, organisations around the world are facing new challenges in managing their human capital. Digital transformation has significantly changed the business landscape, affecting the way organisations operate, communicate and compete in an increasingly competitive marketplace. This research aims to identify HRM best practices that can help organisations overcome the challenges of digital transformation and achieve success in the adoption of new technologies. The focus of this study is primarily qualitative. Methods for gathering data include paying close attention to detail while viewing and recording data, and then using analytical techniques such as data reduction, visualisation, and inference to draw conclusions. The study concluded that HRM strategies in organisations' digital transformation are key to the success of companies in facing the changes of the digital era. By focusing on improving employees' digital competencies, cultural and leadership changes, proper organisational restructuring, talent management, performance measurement, effective communication, flexibility, and good risk management, organisations can optimally leverage digital technology to achieve competitive advantage, improve business performance, and provide added value to customers.